Fertilization and embryonic development of whitefish (Coregonus lavaretus lavaretus) in acidic low-ionic-strength water with aluminum - Keinänen, Marja; Tigerstedt, Christina; Kålax, Pia; Vuorinen, Pekka J. (Academic Press, 2003)
The fertilization rate and extent of the cortical reaction of anadromous whitefish decreased with increasing acidity (0.034 mmol Ca2+L 1); at pH 4.5 the fertilization rate was 46% of that at pH 6.5. Aluminum (250 mgL 1) decreased the percentage fertilization independently of pH and reduced the cortical reaction magnitude at all pH levels. In eggs at pH 5.0, especially at pH 4.5, and in solutions with Al, the growth of embryos was impaired by a perivitelline space that was too narrow. The proportion of embryos with a curved tail tip and those with blood circulation failure increased with decreasing pH. No fry hatched at pH 4.5 and those few that hatched at pH 5.0 did not survive. No fry survived Al-containing water at pH 5.5 and survival was decreased at pH 6.5 with Al. It is concluded that for successful recruitment of anadromous whitefish, pH should preferably remain 45.5 in dilute soft water when toxic concentrations of Al are present.
Keywords: acidic water; aluminum; Coregonus lavaretus lavaretus; siiat; water; pH; aluminium; whitefish; Coregonus lavaretus; fertilization; embryonic development